Evaluation and comparison of flexural strength, surface roughness and porosity percentage of denture base resins incorporated with Thymoquinone and silver nano-antimicrobial agents-an in vitro study - Loveleen Kaur; Meena Ajay Aras; Vidya Chitre; Aradhana Nagarsekar; Amanda Nadia Ferreira (Elsevier, 2022)
Aim: To evaluate and compare the flexural strength, surface roughness and porosity percentage of acrylic denture base material modiﬁed with two antimicrobial agents, Thymoquinone (TQ) and Silver nanoparticles (AgNP). Materials and methods: A total of 90 specimens were fabricated and divided into groups A, B and C with 30 specimens each. Of the 30 specimens, 10 specimens measuring 65mmx 10mmx 2.5 mm were used to study the flexural strength, 10 specimens measuring 10 mm × 20 mm × 3 mm to study surface roughness and 10 specimens measuring 10 mm × 20 mm × 3 mm to study porosity percentage. Group A specimens were made of unmodified denture base resin, group B and C were modified with 2.5% AgNP and 1% TQ respectively. The specimens were processed in the conventional manner. A universal testing machine was used to measure flexural strength and a profilometer was used to measure surface roughness. Porosity percentage was evaluated with help of a desiccator. The data obtained was subjected to statistical analyses using One-way ANOVA and the Tukey-post hoc test, with statistical significance at p ≤ 0.05. Results: Addition of 2.5% AgNP and 1% TQ to acrylic denture base resin significantly reduced flexural strength and increased the porosity percentage (p < 0.01) but within clinically acceptable limits. No significant difference was found in the surface roughness between the various groups tested. Conclusions: Heat cured acrylic denture base resins modified with 2.5% AgNPs,1% TQ exhibited clinically acceptable flexural strength and surface properties and could be incorporated into the denture base material as an antimicrobial agent.